Takhrij and Syarah Hadith of Chemistry: Potential of Soil as a Dog Lick Cleaner - Syifa Akmalia Zahra; Aih Mitamimah; Eko Prabowo Hadisantoso; Erni Isnaeniah; Irwan Abdurrohman (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this research is to discuss the hadith of the Prophet chemicals about soil as a dog lick cleaner. This research method is qualitative through the approach of takhrij and syarah hadith with chemical analysis. The results and discussion of this study are soil as a cleanser for dog saliva. Dog saliva is dangerous because it contains bacteria and the soil has aluminosilicate compounds. The conclusion of this research is takhrij and syarah hadith of the Prophet about soil as a dog lick cleaner with chemical analysis which has the opportunity that the land plays a role as a microbial absorber for viruses present in dog saliva.